THE ROLE OF TRADE UNIONS AND INDUSTRIAL RELATIONS ON EMPLOYEE WELFARE (CASE STUDY AT PT. PERKEBUNAN NUSANTARA III RAMBUTAN) - Candrasa, Limega (Universitas Efarina, 2020)
This study aims to determine the role of trade unions and industrial relations on the welfare of employees at PT. Perkebunan Nusantara III Rambutan, to determine the role of trade unions on the welfare of employees at PT. Perkebunan Nusantara III Rambutan, and to determine the role of industrial relations on the welfare of employees at PT. Nusantara III Ranmbutan Plantation. The type of research used is quantitative research using SPSS Version 25.00. The population in this study was the production section (harvesters) collected in distributing questionnaires totaling 45 respondents. From the results of the study, it was shown that the Labor Union (X1) and Industrial Relations (X2) had no effect on Employee Welfare. Trade Unions and Industrial Relations Simultaneously affect Employee Welfare